2020
DOI: 10.1021/acsabm.0c01133
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Mineralization of Hierarchical Nanofiber Shish-Kebabs in a Concentrated Apatite-Forming Solution

Abstract: Recently, hierarchical polymer nanostructures called nanofiber shish-kebabs (NFSKs) have shown great potential in directing the distribution of minerals for biomineralization. In this work, we report controlled biomimetic mineralization in block copolymer-containing NFSKs. NFSKs were formed by crystallizing polycaprolactone-block-poly­(acrylic acid) (PCL-b-PAA) kebabs on PCL fiber backbones. The block copolymer kebabs were periodically distributed on PCL nanofibers with a spacing of ∼100–300 nm. Free ions coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…PCL-b-PAA was synthesized, with methods and block copolymer characterization previously reported. 43 To form kebab crystals, a 1 w/ v% solution of PCL-b-PAA was dissolved in a mixed solvent of 1:1 PA:EtOH by heating it to 70 °C. After being cooled to room temperature, a 1.5 cm × 1.5 cm square of PCL nanofibers was added to 1 mL of the block copolymer solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCL-b-PAA was synthesized, with methods and block copolymer characterization previously reported. 43 To form kebab crystals, a 1 w/ v% solution of PCL-b-PAA was dissolved in a mixed solvent of 1:1 PA:EtOH by heating it to 70 °C. After being cooled to room temperature, a 1.5 cm × 1.5 cm square of PCL nanofibers was added to 1 mL of the block copolymer solution.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the stage 3 mineralization (as defined in the Introduction) that was previously reported for the same mineralization solution and 12 h time point. 43 PAA 100 (100 kDa) was added to the mineralization solution at low concentration (10 μg/mL), and NFSKs were incubated in these PAA-ion solutions for up to 7 days. Figure 3c−f shows the NFSK mat morphology after mineralizing in the PAA 100 -containing solution.…”
Section: Mineralization Inside and Outside A Dialysis Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Their narrow size distribution combined with their advantages mentioned above makes them ideal templates for preparing spherical inorganic–organic composite materials. 16 For example, synthetic polymer hydrogels composed of poly(acrylamide), 17 PNIPAM, 18 polycaprolactone- block -poly(acrylic acid), 19 and other materials have been used as the template for mineralization. Although there are a number of reports in the literature about the hydrogel with special patterned morphology, the pattern morphology of the composites formed on the surface of materials is derived from the oriented growth of crystals caused by additives or self-assembled templates.…”
Section: Introductionmentioning
confidence: 99%
“…The shish-kebab (SK) structure is a special interface crystal structure in semicrystalline polymers, which consists of straight-chain crystals and folded-chain crystals. Electrospun nanofibers can be used as a straight-chain crystal, which induces the periodic growth of polymers perpendicular to its surface at a certain temperature to form lamellae. When nanofibers and the polymer matrix are similar in geometry, such as lattice parameters, orientation, or some crystal plane spacing, polymer chains can form a kebab or coating on the surface of nanofibers. , Yu et al confirmed that the crystallization behavior of polymers significantly increased the proliferation and alkaline phosphatase (ALP) activity of MC3T3-E1 cells . Chen et al found that the SK structure improved the mechanical properties of nanofibrous membranes …”
Section: Introductionmentioning
confidence: 99%